Seasonal rainfall variability and its correlation with potential drivers over Western Oromia - Ayele Alandu, kefiyalew; Terefe Zeleke, Tadesse; Asfaw Afrassa, Mesfin (International Journal of Physical Research, 2021)
Characterizing seasonal rainfall and identifying its association with the climate drivers are important to produce reliable seasonal climate forecasts of a given area. This study examined the rainfall variability and its relationships with SST, SLP and sunspot indices by statistical methods over Western Oromia. The regional is characterized by monomodal pattern of 60% seasonal rainfall contribution in Kiremt season. High temporal anomaly rainfall but no extremes were observed from 1981-2017. An insignificant decreasing Kiremt and Belg but, an increasing Bega trend was observed. ENSO and PDO/ DMI and AMO showed negative/ positive correlation with kiremt rainfall. ENSO, DMI and AMO showed positive correlation for belg rainfall whereas, PDO showed associated negatively for the most parts of the region. PSI to kiremt/Belg rainfall correlation showed significant positive/Negative spatial association over the western part (West Wolega and Illubabor) / the East part (Jimma & East wollega) of the region. The results showed that there is decreasing trends in rainfall anomalies for main rainy seasons of region and good correlations these various indices. Therefore, it is suggested that seasonal climate predictions may consider these large-scale determinants oscillation indices like AMO and PDO in predicting climatic events.Â Â